The results of Inventori Tugas Perkembangan (ITP) for guidance and counseling services at Islamic boarding schools - Kusaini, Utami Niki (COUNS-EDU: The International Journal of Counseling and Education)
Guidance and counseling service is very useful for students in Islamic Boarding Schools but to determine service based on requirement of students is not easy. This research purposed to describe the results of Inventori Tugas Perkembangan (ITP) to help students find developmental tasks that have not been achieved. This research used survey method. The respondent of this research as many as six classes with the amount of 445 students in two Islamic Boarding School of Yogyakarta. The results showed that the achievement of development tasks students above the average growth rate of 3.75. The task of development is not yet achieved (<3.75). Based on these results, the researcher sees each class having differences in aspects of development tasks that have not been achieved and require different guidance and counseling services.